Momentum profits and time-varying unsystematic risk - Li, Xiafei; Miffre, Joëlle; Brooks, Chris; O’Sullivan, Niall (Journal of Banking & Finance, 2008)
This study assesses whether the widely documented momentum profits can be attributed to time-varying risk as described by a GJR-GARCH(1,1)-M model. We reveal that momentum profits are a compensation for time-varying unsystematic risks, which are common to the winner and loser stocks but affect the former more than the latter. In addition, we find that, perhaps because losers have a higher propensity than winners to disclose bad news, negative return shocks increase their volatility more than they increase those of the winners. The volatility of the losers is also found to respond to news more slowly, but eventually to a greater extent, than that of the winners.